ENHANCING LEARNERS’ REFLECTIONS IN THE PROCESS OF LEARNING ELF PRONUNCIATION THROUGH TECHNOLOGY-BASED SELF-STUDY - Wach, Aleksandra (Neofilolog, 2019)
This article reports the findings of a qualitative study aimed at investigating how the use of technology-based resources in out-of-class self-study by learners of English affects their level of reflectivity during the process of learning pronunciation. Using as a research tool learners’ diaries submitted on Moodle, the study also explores the value of such diaries in promoting reflection in learners. The findings largely confirmed the considerable role played by technology-based self-study and diary writing in enhancing reflection on learning pronunciation in the participants. These reflections concerned their growing phonological awareness, the use of materials appropriate for pronunciation practice, pronunciation learning strategies, and the affective side of learning. The didactic implications include the need to employ a wide range of technology-based resources for self-study and to encourage learners to keep reflective diaries as part of their pronunciation instruction.